Diagnostic yield and clinical utility of whole exome sequencing using an automated variant prioritization system, EVIDENCE. Issue 6 (17th September 2020) - Seo, Go Hun; Kim, Taeho; Choi, In Hee; Park, Jung‐young; Lee, Jungsul; Kim, Sehwan; Won, Dhong‐gun; Oh, Arum; Lee, Yena; Choi, Jeongmin; Lee, Hajeong; Kang, Hee Gyung; et al.
Abstract: EVIDENCE, an automated variant prioritization system, has been developed to facilitate whole exome sequencing analyses. This study investigated the diagnostic yield of EVIDENCE in patients with suspected genetic disorders. DNA from 330 probands (age range, 0‐68 years) with suspected genetic disorders were subjected to whole exome sequencing. Candidate variants were identified by EVIDENCE and confirmed by testing family members and/or clinical reassessments. EVIDENCE reported a total 228 variants in 200 (60.6%) of the 330 probands. The average number of organs involved per patient was 4.5 ± 5.0. After clinical reassessment and/or family member testing, 167 variants were identified in 141 probands (42.7%), including 105 novel variants. These variants were confirmed as being responsible for 121 genetic disorders. A total of 103 (61.7%) of the 167 variants in 95 patients were classified as pathogenic or probably to be pathogenic before, and 161 (96.4%) variants in 137 patients (41.5%) after, clinical assessment and/or family member testing. Factor associated with a variant being regarded as causative includes similar symptom scores of a gene variant to the phenotype of the patient. This new, automated variant interpretation system facilitated the diagnosis of various genetic diseases with a 42.7% diagnostic yield. Abstract : Schematic diagram showing the number of patients with and without variant identification and family member testing and the proportion of variant classification.